Adoption of Online Classes During COVID-19: An Institution’s Investigation on Perception & Behavioral Intention - UDANG, LESTER (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
In the advent of COVID-19, there is abounding curiosity whether the shift to online classes is effective. Moreover, as to which factors affect effectiveness, would become important for policymakers, stakeholders, and administrators currently mitigating educational disruption. As for Rajamangala University of Technology, Tawan-ok (RMUTTO), factors encouraging positive perception and behavioral intention towards adoption of online classes were explored among its learners and lecturers. These factors were adopted from the Unified Theory of Acceptance and Use of Technology model (UTAUT), sample responses were analyzed through the Exploratory Factor Analysis & Structural Equation Modeling; and results were shown among factor relationships. Performance Expectancy & Facilitating Conditions influenced Attitude, and Effort Expectancy & Social Influence influenced Behavioral Intention – in both groups. Performance Expectancy over Behavioral Intention and Social Influence over Attitude were especially significant among learners; while, Effort Expectancy on Attitude was particularly significant among lecturers. Also, a disconnect among Facilitating Conditions & Behavioral Intention, and surprisingly, Attitude & Behavioral Intention were shown in this study. Furthermore, their current adoption was implored. Both groups felt that the current policy was necessary, beneficial but, to an extent, not practical. Both groups believed challenges were related to paucity and capacity in running online classes. Learners specifically addressed future issues in online learning related to its effectiveness, and lecturers emphasized its equity in online teaching – if classes were to resume online much longer. Practical implications of this study in technology acceptance would contribute significantly towards better adoption of online classes during this outbreak.